Idiopathic Intracranial Hypertension Papillopathy due to Hormonal Changes during Pregnancy - Marco Mafrici; Francesca Tona; Serena Fragiotta; Umberto Lorenzi; Lorenzo Gitto; Laura Toscani (Case Reports in Ophthalmological Medicine)
Background. The underlying mechanisms of papilledema associated with intracranial hypertension remain unclear. A case of bilateral papillary edema in a patient with chronic idiopathic intracranial hypertension who was asymptomatic during her two pregnancies is reported. Case Presentation. A 19-year-old Caucasian female, in her third month of pregnancy, complained of difficulties with close reading. The patient’s visual acuity was 20/20 on the Snellen chart and improved with a 0.50 D correction in both eyes. Near vision and slit lamp examinations revealed normal findings bilaterally. However, a fundus examination showed bilateral papillary edema without evidence of hemorrhages or neovascularization. Blood tests were unremarkable, except for a slight increase in C-reactive protein levels. The patient had a prepregnancy weight of 63 kilograms, with a BMI of 24.91 kg/m2. Magnetic resonance imaging of the brain revealed features consistent with chronic idiopathic intracranial hypertension, which resolved after delivery. Two and a half years later, during a subsequent pregnancy, the patient experienced a recurrence of bilateral papillary edema due to the IIH. It was managed similarly as the first occurrence, resulting in bilateral anatomical and functional recovery. Recent research revealed that, during pregnancy, hormones interact with the central nervous system, leading to an increase in the size of neurons which could potentially result in intracranial hypertension. Conclusions. The influence of hormonal fluctuations during pregnancy on the development of transient central nervous system abnormalities in individuals with chronic intracranial hypertension, leading to papillary edema, remains a matter of debate.